Evaluasi Aktivitas Manual Material Handling Dengan Menggunakan Metode Biomekanika Kerja Pada Pengangkatan Thiner di Bagian Warehouse - Ade Andhika Saputra; Wahyudin; Asep Erik Nugraha (TALENTA Publisher, 2021)
In doing a job manually such as moving, lifting a certain material needs to be evaluated to minimize the risk of work accidents. The research that will be conducted is the evaluation of manual material handling on the removal and removal of thiners. The purpose of this study was to determine the application of work biomechanics in minimizing the risk of spinal cord injury and providing improvement in work activities. The methods used in this research are Nordic Body Map, NIOSH, Rapid Entire Body Assessment, L5 / S1 (Fc) Force and Energy Consumptions. The results of this study were found that several parts of the workers' body muscles were injured, such as the neck, left and right shoulders, arms and wrists, back and waist. The RWL and Li values ​​after repairs where is RWL exceeded the Load Constant value of 20 kg, and the Li value <1 (no risk). Then the work category level which was originally light-moderate work changed to light work. Furthermore, the original REBA score got a score of 5 to 3 (level 1). And the results of the compressive force against L5 / S1 have values ​​of Fc <AL and Fc < MPL.